Environmental conditions associated with carbonate-bearing rocks in lower Hawksbill Gap, Jezero western fan, Mars - Rebecca M.E. Williams; Joel A. Hurowitz; Linda C. Kah; Gwénaël Caravaca; Sanjeev Gupta; Nicolas Mangold; Michelle E. Minitti; R. Aileen Yingst; Kyle Uckert; Roger C. Wiens; Michael Tice; Megan Kennedy Wu; et al. (Icarus, 2026)

Harnessing a deep-sea EAL-domain enzyme for quorum quenching and biofilm control in food pipelines - Ramu Meenatchi; P. Snega Priya; Nitya Sunanda Appikatla; Raja Mohanakrishna; Damotharan Kesavan; J.T. Mary Leema; Sree Sankar Darveekaran Nair; Saurav Gupta; Pushplata Yadav; Saravanane Narayanane; Karpaga Raja Sundari Balachandran; Vijaya Raghavan Rangamaran; et al. (International Journal of Food Microbiology, 2025)

Novel extraction technique: quantification of major phytoconstituents of arjuna in infused edible oil - Rajesh Kumar Verma; Neelam Pal; Sujeet Gupta; Varun Kumar Singh; Priyanka Gupta; Sunanda Handoo; Charan Singh Rana (Natural Product Research, 2025)

Microbial diversity and function in crystalline basement beneath the Deccan Traps explored in a 3 km borehole at Koyna, western India - Rajendra Prasad Sahu; Sufia K. Kazy; Himadri Bose; Sunanda Mandal; Avishek Dutta; Anumeha Saha; Sukanta Roy; Srimanti Dutta Gupta; Abhijit Mukherjee; Pinaki Sar (Environmental Microbiology, 2022)
Summary Deep terrestrial subsurface represents a huge repository of global prokaryotic biomass. Given its vastness and importance, microbial life within the deep subsurface continental crust remains under‐represented in global studies. We characterize the microbial communities of deep, extreme and oligotrophic realm hosted by crystalline Archaean granitic rocks underneath the Deccan Traps, through sampling via 3000 m deep scientific borehole at Koyna, India through metagenomics, amplicon sequencing and cultivation‐based analyses. Gene sequences 16S rRNA (7.37 × 10 6 ) show considerable bacterial diversity and the existence of a core microbiome (5724 operational taxonomic units conserved out of a total 118,064 OTUs) across the depths. Relative abundance of different taxa of core microbiome varies with depth in response to prevailing lithology and geochemistry. Co‐occurrence network analysis and cultivation attempt to elucidate close interactions among autotrophic and organotrophic bacteria. Shotgun metagenomics reveals a major role of autotrophic carbon fixation via the Wood–Ljungdahl pathway and genes responsible for energy and carbon metabolism. Deeper analysis suggests the existence of an ‘acetate switch’, coordinating biosynthesis and cellular homeostasis. We conclude that the microbial life in the nutrient‐ and energy‐limited deep granitic crust is constrained by the depth and managed by a few core members via a close interplay between autotrophy and organotrophy.

Ionic selectivity and coordinated transport of Na+ and K+ in flag leaves render differential salt tolerance in rice at the reproductive stage - Koushik Chakraborty; Krishnendu Chattaopadhyay; Lopamudra Nayak; Soham Ray; Lucina Yeasmin; Priyanka Jena; Sunanda Gupta; Sangram K. Mohanty; Padmini Swain; Ramani K. Sarkar (Planta, 2019)

Genetic diversity changes in Indian lentils over the times - Jitendra Kumar; Sunanda Gupta; Sonali Dubey; Priyanka Gupta; Debjyoti Sen Gupta; N P Singh (Journal of Plant Biochemistry and Biotechnology, 2018)

Identification of QTLs for agronomic traits using association mapping in lentil - Jitendra Kumar; Sunanda Gupta; Debjyoti Sen Gupta; Narendra Pratap Singh (Euphytica, 2018)

Association of functional markers with flowering time in lentil - Jitendra Kumar; Sunanda Gupta; Revanappa S. Biradar; Priyanka Gupta; Sonali Dubey; Narendra Pratap Singh (Journal of Applied Genetics, 2018)

Quantitative trait loci from identification to exploitation for crop improvement - Jitendra Kumar; Debjyoti Sen Gupta; Sunanda Gupta; Sonali Dubey; Priyanka Gupta; Shiv Kumar (Plant Cell Reports, 2017)